KIM EOK’S TRANSLATION AND HAN YONG-UN’S THE LOVER’S SILENCE – THE INTERIORITY IN THE 1920s’ LITERATURE - YANG, Soon-Mo (International Journal of Korean Humanities and Social Sciences, 2019)
The article tries to examine and define the inner self of literature in the 1920s, now considered the birth of modern Korean literature. The interiority of 1920’s literature is widely accepted as the transition period between the birth (the 1910s, the Enlightenment) and maturation (1930s, Modernism), and as a reflection of the tragic situation after 1919. However, in the light of the symptom that determines the structure of desire, the inner self of 1920’s literature could be identified as a “person who denies loss”, a pervasive attitude. And it also could provide a critical reading along with some directivity, which is meaningful to concepts such as self-relation and the other relations that construct the individual. This paper examines this perspective of inner self within 1920’s literature of Kim Eok and Han Yong-un, so as to set an intrinsic standard that would enable scholars to evaluate the literary value of the 1920’s. Above all, through the Symptomatic Identification approach, this study will conduct archeological and genealogical research that could be helpful to today’s discourse.